Association of plasma MMP-2 levels and prognosis of patients with intracerebral hemorrhage: a prospective cohort study - Yu, Wenmin; Peng, Jin; Chen, Zhiying; Li, Huimin; Yang, Jianyuan; Wu, Yun; Zhang, Manqing; Wu, Moxin (Frontiers in Neurology, 2023)
Objective The role of MMP-2 in patients with ICH is controversial and the impact of plasma MMP-2 level on clinical outcome is still unclear. Materials and methods In this study, the peripheral venous blood was acquired from 93 patients with ICH and 88 healthy controls within 24 h of hospitalization and at enrollment. We retrospectively investigated plasma MMP-2 levels of patients and healthy controls. The edema volume, the NIHSS score, the GCS score, and mRS were used to assess and quantify neurological deficit following ICH. Logistic regression analysis was configured to determine the independent relation of plasma MMP-2 levels with clinical outcomes. In addition, the plasma MMP-14 levels and complement C4 level were tested to explore the relationship with plasma MMP-2 level. Results There was a significant reduction of plasma MMP-2 levels in ICH patients than that in healthy controls (38.02 ± 1.71 vs. 54.03 ± 2.15, p < 0.0001), and MMP-2 is negatively correlated with the edema volume (r = −0.2187, p < 0.05), NIHSS score (r = −0.2194, p < 0.05), blood leucocyte count (r = −0.2549, p = 0.012), and complement C4 level (r = −0.2723, p = 0.005). There is positive correlation between MMP-2 level and GCS score (r = 0.2451, p = 0.01) and MMP-14 level (r = 0.7013, p = 0.005). The multivariate analysis revealed that reduced plasma MMP-2 level is associated with elevated edema volume (OR = 0.2604, 95% CI [0.07 to 0.84], p = 0.02). Conclusion The plasma MMP-2 level in patients with ICH is significantly lower than that of healthy controls, and plasma MMP-2 level may be a prognostic factor. Plasma MMP-2 levels are correlated with the clinical outcomes of patients and negatively correlated with blood leucocyte count and complement C4 level in patients with ICH.